Nanoparticle Drug Delivery Can Reduce the Hepatotoxicity of Therapeutic Cargo. Issue 7 (23rd January 2020) - Yang, Feifei; Medik, Yusra; Li, Liantao; Tian, Xi; Fu, Dong; Brouwer, Kim L. R.; Wagner, Kyle; Sun, Bo; Sendi, Hossein; Mi, Yu; Wang, Andrew Z.
Abstract: Hepatotoxicity is a key concern in the clinical translation of nanotherapeutics because preclinical studies have consistently shown that nanotherapeutics accumulates extensively in the liver. However, clinical‐stage nanotherapeutics have not shown increased hepatotoxicity. Factors that can contribute to the hepatotoxicity of nanotherapeutics beyond the intrinsic hepatotoxicity of nanoparticles (NPs) are poorly understood. Because of this knowledge gap, clinical translation efforts have avoided hepatotoxic molecules. By examining the hepatotoxicity of nanoformulations of known hepatotoxic compounds, it is demonstrated that nanotherapeutics are associated with lower hepatotoxicity than their small‐molecule counterparts. It is also found that the reduced hepatotoxicity is related to the uptake of nanotherapeutics by macrophages in the liver. These findings can facilitate further development and clinical translation of nanotherapeutics. Abstract : Hepatotoxicity is a key concern in the clinical translation of nanomedicine due to nanotherapeutics' high accumulation in the liver. It is shown that nanotherapeutics have lower hepatotoxicity than their small‐molecule counterparts. It is further shown that the uptake of nanotherapeutics by macrophages in the liver is the key factor in the reduced hepatotoxicity.